Illuminating the science of art history the advent of the slide lecture in France - Timby, Kim (2024)
In the late 1880s and early 1890s, a small number of professors – including Charles Diehl, Louis Courajod and Henry Lemonnier – started projecting photographic reproductions in their art history classes in France. They were among the first to teach the subject in the country’s universities. This newly accessible technology enabled artwork-based demonstrations in the classroom for large audiences, complementing and eventually replacing paper photographs, plaster casts and other methods of reproduction. From the mid-1890s, demand for slide projections in universities was reinforced by the popularity of educational slideshows in French culture. They would become omnipresent in art history departments by World War I. This article explores when and why the projected photograph was adopted by art historians in lecture halls, the ways in which individual professors employed and discussed slides, and how their respective institutions invested in this activity. I argue that for the educators who instituted slide projection, the practice was about grounding the young discipline’s methodology in the analysis of empirical data. It gave concrete form to scientific enquiry and was attractive to students. Showing slides was thus a powerful practical and ideological tool in the establishment of art history as an academic discipline in France.
Keywords: Lemonnier, Henry -- 1842-1936; Courajod, Louis -- 1841-1896; Diehl, Charles -- 1859-1944; Geschichte 1885-1900; Kunstgeschichte -- Fach; Vorlesung; Diavortrag; Frankreich